AFFECTING FACTORS STOCK PRICE: EARNINGS PER SHARE AS MODERATING VARIABLE - Mardiyani, Mardiyani (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: Determine how financial measures affect stock prices using the Earnings Per Share mediation variable. Design/methodology/approach: Research methodologies using quantitative techniques. The study population consisted of consumer cyclical companies listed on the Indonesia Stock Exchange between 2020 and 2022. Deliberate selection methods were used in the selection of these firms. The study used Moderated Regression Analysis Test using SPSS software version 29. Findings: Earnings per share acts as a mediator between the stock price and the debt-to-equity ratio, however Earnigs Per Share cannot considerably alter the stock price or lessen the impacts of return on assets. Research limitations/implications: Small sample, short periods, companies neglect operational assets. Practical implications: The Effects of Stock Price and Earnings Per Share with a Moderate Debt to Equity Ratio. Originality/value: Empirical evidence indicates that profits per share mediate between the influence of debt policy and stock prices. Paper type: Research Paper